The effects of thinking skills education on the creative thinking skills of preschool teacher candidates [Düşünme becerileri eǧitiminin okul öncesi öǧretmen adaylarinin yaratici düşünme becerilerine etkisi] - (:unkn) unknown (My University, 2012)
The aim of this study was to test the effects of "Thinking Skills Training Program" which is based on Sternberg's "Theory of Successful Intelligence" on preschool teacher candidates' creative thinking. A quasi-experimental design was applied with three samples. Treatment group (n=34), Comparison I (n=34) and Comparison II group (n=33). Data were collected by Torrance Creative Thinking Test (TCTT). According to the results derived from the treatment group, the total scores obtained from the pre and post-tests indicate significant results on the dimensions of creative thinking skills (Verbal fluency, verbal flexibility, verbal originality, figural fluency, figural originality, abstractness of the titles, figural elaboration, emotional expressiveness, unusual visualization, richness of imagery, movement or action). The treatment groups' post tests scores of dimensions of creative thinking skills (verbal fluency, verbal originality, figural originality, abstractness of titles, richness of imagery, fantasy) performed significantly better than the comparison groups.
Keywords: Creative thinking; Preschool education; Teacher education